2005
DOI: 10.1103/physreva.71.013416
|View full text |Cite
|
Sign up to set email alerts
|

Ionization of Rydberg atoms embedded in an ultracold plasma

Abstract: We have studied the behavior of cold Rydberg atoms embedded in an ultracold plasma. We demonstrate that even deeply bound Rydberg atoms are completely ionized in such an environment, due to electron collisions. Using a fast pulse extraction of the electrons from the plasma we found that the number of excess positive charges, which is directly related to the electron temperature Te, is not strongly affected by the ionization of the Rydberg atoms. Assuming a Michie-King equilibrium distribution, in analogy with … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
47
0

Year Published

2007
2007
2010
2010

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 35 publications
(50 citation statements)
references
References 22 publications
3
47
0
Order By: Relevance
“…Soon after this work, a sample of purely cold Rydberg atoms was observed to ionize spontaneously, and electron emission from such a sample was observed for more than 20 ms after the excitation of the initial Rydberg state [15]. A similar phenomenon had been observed previously in a thermal sample of cesium Rydberg atoms by Vitrant et al [16] at a density a factor of 10 4 higher than those used in Refs. [14] and [15].…”
Section: Introductionsupporting
confidence: 64%
See 1 more Smart Citation
“…Soon after this work, a sample of purely cold Rydberg atoms was observed to ionize spontaneously, and electron emission from such a sample was observed for more than 20 ms after the excitation of the initial Rydberg state [15]. A similar phenomenon had been observed previously in a thermal sample of cesium Rydberg atoms by Vitrant et al [16] at a density a factor of 10 4 higher than those used in Refs. [14] and [15].…”
Section: Introductionsupporting
confidence: 64%
“…Such a plasma can be created by photoionization of atoms in a magneto-optical trap (MOT) using a pulsed laser. The initial observation of this phenomenon was made using 50 K Xe atoms, but since then similar results have been found using cold Rb, Cs, and Sr atoms [2][3][4][5]. To a very good approximation, the initial electron energy is determined by the excess photon energy above the ionization limit of the photoionizing laser, while the initial positive ion temperature is that of the initially trapped atoms before ionization.…”
Section: Introductionmentioning
confidence: 99%
“…In later experiments, it was found that electron-Rydberg-atom collisions that occur once the trap depth is sufficient do in fact cause redistribution of the population from the initial Rydberg state to nearby high-nl states. As a result of these collisions, approximately 2 3 of the Rydberg atoms ionize while 1 3 are de-excited to lower energy states. Li.…”
Section: Rydberg Gas Evolution To Plasmamentioning
confidence: 99%
“…This is an experimentally attractive setup because of its simplicity of construction and optimal optical access. The quadrupole trap is commonly used because of these attributes [2,3,4,5].…”
Section: Laser Cooling and Trappingmentioning
confidence: 99%
See 1 more Smart Citation